2009
DOI: 10.1002/eji.200939677
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 is essential for the proliferation of T‐cell progenitors and mature peripheral T cells

Abstract: The serine/threonine kinase LKB1 has a conserved role in Drosophila and nematodes to co-ordinate cell metabolism. During T lymphocyte development in the thymus, progenitors need to synchronize increased metabolism with the onset of proliferation and differentiation to ensure that they can meet the energy requirements for development. The present study explores the role of LKB1 in this process and shows that loss of LKB1 prevents thymocyte differentiation and the production of peripheral T lymphocytes. We find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
96
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 52 publications
10
96
0
1
Order By: Relevance
“…In this study, we identified LKB1 as an essential regulator of intrathymic T-cell development. A very recent publication from the Cantrell lab also reported that deletion of LKB1 prevents T-cell development [36]. Both studies showed that LckCre-mediated deletion of LKB1 in T cells led to reduced thymus size, blocked transition from DN3 to DN4 stage and impaired generation of CD4 SP and CD8 SP thymocytes.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we identified LKB1 as an essential regulator of intrathymic T-cell development. A very recent publication from the Cantrell lab also reported that deletion of LKB1 prevents T-cell development [36]. Both studies showed that LckCre-mediated deletion of LKB1 in T cells led to reduced thymus size, blocked transition from DN3 to DN4 stage and impaired generation of CD4 SP and CD8 SP thymocytes.…”
Section: Discussionmentioning
confidence: 98%
“…In this issue of the European Journal of Immunology, Tamas et al attempt to identify a novel ''master regulator'' of lymphocyte growth and metabolism by genetically targeting the liver kinase B1 (LKB1) [6]. LKB1 is a serine-threonine kinase that regulates a number of important kinases of the AMP-activated protein kinase (AMPK) family [7].…”
Section: Commentarymentioning
confidence: 99%
“…Interestingly, T-cell-specific LKB1 deletion does not lead to transformation but to severe effects on cell growth, proliferation, and progenitor maturation [6]. Lck-Cre-mediated deletion of LKB1 leads to an almost complete suppression of intrathymic development [6].…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations